1993
DOI: 10.2307/1591458
|View full text |Cite
|
Sign up to set email alerts
|

Transfer of IgG from Serum to Lachrymal Fluid in Chickens

Abstract: Pure 125I-radiolabeled chicken IgG was inoculated intravenously into 2-week old chickens. Radioactivity in lachrymal fluid samples was first detected 10 minutes postinoculation (PI). Radioactivity levels declined up to day 20 PI, when they reached marginal levels. Sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE) followed by autoradiography of lachrymal fluid samples, taken daily for 16 days, showed the presence of radioactive polypeptides in the same positions as their stained control count… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

1995
1995
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(23 citation statements)
references
References 5 publications
2
19
0
Order By: Relevance
“…Antigen-specific serum immunoglobulin has been shown to confer protection against air sac lesions when hightiter M. gallisepticum-specific antiserum was passively transferred to naive chickens (21). There is also evidence of transudation of serum antibodies onto mucosal surfaces (33,34). The similar kinetics of specific IgG in the tracheal washes (Fig.…”
Section: Discussionmentioning
confidence: 79%
“…Antigen-specific serum immunoglobulin has been shown to confer protection against air sac lesions when hightiter M. gallisepticum-specific antiserum was passively transferred to naive chickens (21). There is also evidence of transudation of serum antibodies onto mucosal surfaces (33,34). The similar kinetics of specific IgG in the tracheal washes (Fig.…”
Section: Discussionmentioning
confidence: 79%
“…Finally, the tears may have been over-diluted, since the elution was done according to a protocol established for blood (Thangavelu et al ., 2000). This is probable, as the amounts of IgG in the tears, mostly due to transudation (Toro et al , 1993), are likely to be less concentrated than the blood.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, various researchers have studied the role of the Harderian gland in IBV-infected chickens and the presence of antibodies in the lachrymal fluid (Survashe et al ., 1979;Davelaar et al ., 1982;Cook et al ., 1992;Toro et al , 1993;Dhinakar Raj & Jones, 1996;Toro et al ., 1996). In order to do this, especially in young chicks, the induction of excess lachrymal fluid is essential and two main methods are commonly used.…”
Section: Infectious Bronchitis Virus (Ibv) Induces a Range Of Immune mentioning
confidence: 99%
See 1 more Smart Citation
“…Olah et al (1996) found that the ASC produce mainly IgA and IgM, whereas Jeurissen et al (1994) showed the presence of a considerable number of IgY-producing cells. Locally produced Ig of all isotypes appears in tears together with IgY transudated from serum (Toro et al 1993), thus protecting the upper RT. The ASC are present in comparable numbers in chickens raised under SPF and under conventional conditions (Bang and Bang 1968).…”
Section: Humoral Immune Responses In the Rtmentioning
confidence: 99%